State of the world ... : a Worldwatch Institute report on progress toward a sustainable society. - Worldwatch Institute Washington (New-York : Norton, 1984)
Worldwatch's flagship annual report remains the most authoritative "go-to" resource for those who understand the importance of nuturing a safe, just, and healthy global environment through policy and action. First published in 1984 as a compendium of issues, State of the World now covers selected sustainability topics annually, including urban development, climate change, global security, consumerism, and agricultural innovation.
Verschijnt jaarlijks.
Keywords: Internationaal milieubeleid; Milieu